THE ANALYSIS OF THE EUROPEAN BANKING MARKET STRUCTURE - A. M. Motokhin; I. A. Smaragdov (Финансы: теория и практика)
The banking system must be seen as a whole comprising different national banks and loan institutions which activities are governed by the monetary mechanism. The banking system includes the network of commercial banks as well as other credit and settlement centers. The central bank is responsible for the state emission and foreign exchange policy and constitutes the core of the reserve system. [1, p. 234]. Commercial banks carry out a wide range of functions: keeping of customer current accounts, crediting of individuals and legal entities, purchase and sale of government and corporate securities, and many others [2]. Today most European banks are highly developed banking institutions providing a broad range of banking services. Therefore, the analysis of the European banking sector is of particular interest to banking analysts.The article analyzes the structure of the European banking market,determines the level of market competition,and identifies the commercial bank which position on the analyzed market is close to monopolistic.